Tomato Mutants SlIAA9 Exhibit Thermo-Morphophysiological Characters and Enhanced SIDREBA4 Gene Expression - Cory Rafsyanyani; Titah Rigel Anjalani; Anisa Esti Rahayu; Syariful Mubarok; Ani Widiastuti; Deden Derajat Matra; Hiroshi Ezura; Nurul Jadid (Caraka Tani: Journal of Sustainable Agriculture, 2026)
Rising temperatures associated with climate change threaten tomato productivity, yet the contribution of auxin signaling components to heat-stress adaptation remains incompletely understood. The IAA9 gene, encoding an Aux/IAA transcriptional repressor, is well known for its role in auxin-regulated development, but its role in heat responses is still unclear. This study aims to elucidate the function of IAA9 in modulating tomato responses under heat stress conditions. Researchers utilized tomato iaa9-3 and iaa9-5 mutants and exposed them to prolonged elevated temperatures of 40 to 45 °C for 6 weeks to assess morphophysiological traits, and to 38 to 40 °C for 6 days to evaluate molecular responses through SlDREBA4 gene expression analysis. Under prolonged heat stress, all genotypes exhibited reduced leaf area, leaf number, and total chlorophyll content, accompanied by increased plant height compared to plants grown under normal conditions. Specifically, wild-type Micro-Tom (WT-MT) showed the lowest values in leaf area (165.89 cm²), leaf number (23 leaves), and total chlorophyll content (115.7 µg g-1). In contrast, the iaa9-3 and iaa9-5 mutants recorded the highest plant heights at 11.98 and 12.13 cm, respectively, indicating a differential growth response under stress. Gene expression analysis revealed that SlDREBA4 expression was upregulated in both iaa9-3 and iaa9-5 mutants compared to normal temperature conditions, with increases of 0.45-fold and 1.78-fold, respectively. These results indicate that IAA9 mutations confer enhanced thermotolerance in tomato, as reflected by altered morphology and increased heat-responsive gene expression. This study highlights IAA9 as a potential genetic target for improving heat stress resilience in tomato breeding programs.